Histological structure and histochemical composition of the digestive tract of salema porgy, Sarpa salpa (Linnaeus, 1758) (Teleostei: Sparidae) - Ozretić, Judita (Array, 2021)
The histological structure and histochemical characteristics of the digestive tract of five specimens of salema porgy (Sarpa salpa, L.) were analysed using haematoxylin-eosin, Alcian blue/PAS and orcein-Giemsa staining techniques. The digestive system of salema porgy consists of esophagus, stomach and intestines with associated organs such as liver, pancreas and gallbladder. The wall of esophagus, stomach, intestines and gallbladder has four distinctive layers: the mucosa, the submucosa, the muscular and outer layer, serosa or adventitia. The mucosa consists of two different layers: epithelium and lamina propria. Mucosa of the upper part of the digestive system is layered by single squamous epithelium, while those of lower part of the digestive system is layered by single columnar epithelium. The submucosa is a layer made of connective tissue and blood vessels. In most parts of the digestive system the muscular layer consists of two parts: circular and longitudinal. The exception is the muscular layer of the stomach fundus which has three layers: inner, medium and outer. The outermost layer in the esophagus is adventitia made of connective tissue, blood vessels and nerves. In the stomach, intestines and the gallbladder this layer is replaced by serosa. Histochemical analysis has shown that mucosal cells in all parts of the digestive tube contain acid mucopolysaccharides (MPS). The liver consists of hepatocytes separated by sinusoidal capillaries. The pancreatic tissue is scattered along the liver parenchyma and along the wall of pyloric caeca.The present study is the first record on digestive system histology of salema porgy showing that it is congruent to its feeding habits.